Fungus-targeted nanomicelles enable microRNA delivery for suppression of virulence in Aspergillus fumigatus as a novel antifungal approach - Inukai, Tatsuya; Watanabe, Rikuto; Murakami, Yoshiki; Cabral, Horacio; Kuroda, Masahiko; Nakamura, Shigeki (Scientific reports, 2025)
Aspergillus fumigatus , which causes aspergillosis, has developed resistance to azole antifungal agents in recent years. As only three main classes of antifungal drugs are available, the development of novel therapeutic strategies is crucial. We aimed to control the expression of virulence factors by introducing microRNAs (miRNAs) into fungi as an innovative therapeutic approach. To test our hypothesis, we selected miRNA mimics targeting alb1 , which is involved in the synthesis of 1,8-dihydroxynaphthalene (DHN)-melanin, a virulence factor of A. fumigatus , and transfected them into the protoplast of the fungus, resulting in a two-fold reduction in alb1 expression. Next, we created a 3×HA-tagged Alb1 protein (Alb1-HAp)-expressing strain and confirmed the regulation of translation using western blotting with an anti-HA antibody. The protein amount of Alb1-HAp was reduced by one-third after the introduction of the miRNA. Moreover, the reduction in melanin after miRNA transfection promoted the killing of fungus by hydrogen peroxide-induced oxidative stress and sensitised the fungus to neutrophil attack. Additionally, by loading miRNAs into a fungus-targeted delivery system, we demonstrated the potential of transferring miRNAs into intact fungal cells in vitro. These results indicate the potential of miRNAs to regulate target virulence factors in fungi, leading to the development of novel therapies.